The great guide what David Hume can teach us about being human and living well - Baggini, Julian (Princeton University Press, 2021)
"David Hume (1711-1776) is perhaps best known for his ideas about cause and effect and his criticisms of religion, but he is rarely thought of as a philosopher with practical wisdom to offer. Yet Hume's philosophy is grounded in an honest assessment of nature - human nature in particular. The Great Guide is an engaging and eye-opening account of how Hume's thought should serve as the basis for a complete approach to life. In this enthralling book, Julian Baggini masterfully interweaves biography with intellectual history and philosophy to give us a complete vision of Hume's guide to life. He follows Hume on his life's journey, literally walking in the great philosopher's footsteps as Baggini takes readers to the places that inspired Hume the most, from his family estate near the Scottish border to Paris, where, as an older man, he was warmly embraced by French society. Baggini shows how Hume put his philosophy into practice in a life that blended reason and passion, study and leisure, and relaxation and enjoyment. The Great Guide includes 145 Humean maxims for living well, on topics ranging from the meaning of success and the value of travel to friendship, facing death, identity, and the importance of leisure. This book shows how life is far richer with Hume as your guide"--Publisher's description